THE IMPACT OF DIGITAL LITERACY ON POLITICAL TRUST - Maritza, Regina; Wibowo, Kunto Adi; Rahmawan, Detta; Fuady, Ikhsan (LPPM Univ. Ibn Khaldun Bogor, 2026)
The phenomenon of political hoaxes poses a serious challenge to political communication in the digital era, particularly with the widespread use of social media. Hoaxes not only distort information but also have the potential to reduce political trust and undermine the quality of democracy. This study aims to analyze the relationship and influence of digital literacy on political trust among young social media users. The study employed a positivistic paradigm with a quantitative approach through a survey method. The study population was college students who used Instagram, with a sample of 399 respondents in West Java. Data were collected through a five-point Likert-scale questionnaire measuring digital literacy and political trust, then analyzed using SPSS. The test results showed that all research instruments were valid and reliable. Spearman correlation analysis showed a positive and significant relationship between digital literacy and political trust (r = 0.355; p < 0.05). Furthermore, binary logistic regression analysis showed that digital literacy significantly influenced the likelihood of respondents having a high level of political trust (Exp(B) = 1.268). These findings confirm that digital literacy plays a protective role in dealing with political hoaxes and is important in maintaining the quality of political communication and democracy in the digital era.